Porites decasepta: a new species of scleractinian coral (Scleractinia, Poritidae) from Oman - Claereboudt, Michel R. (Zootaxa, 2006)
A new species of scleractinian coral, Porites decasepta spec. nov. (Scleractinia, Poritidae) is described from the Bar Al-Hikman reef complex along the Arabian Sea coast of the Sultanate of Oman. Porites decasepta spec. nov. forms encrusting, bright blue colonies rarely exceeding 7 cm in diameter. Corallites, about 1mm in diameter, have only 10 septa: the two lateral septa of the ventral triplet typical of Porites septal arrangement are missing or strongly reduced. Une nouvelle espèce de scleractiniaire, Porites decasepta spec. nov. (Scleractinia Poritidae) est décrite du complex récifal de Bar Al-Hikman situé le long de la côte de la mer d’arabie du Sultanat d’Oman. La nouvelle espèce forme de petites colonies encroûtantes, de couleur bleu-violet, ne dépassant guère 7 cm de diamètre. Les corallites d’à peu près 1mm de diamètre n’ont que 10 septa: les deux septa latéraux du triplet ventral étant le plus souvent manquants ou fortement réduits.